2014
DOI: 10.1080/07448481.2014.917651
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of, and Assistance Provided to, a Hypothetical Rape Victim: Differences Between Rape Disclosure Recipients and Nonrecipients

Abstract: Objective Undergraduate rape disclosure recipients and nonrecipients’ sociodemographic and life experience variables, attitudes towards rape and responses to a hypothetical rape disclosure were compared to determine differences between them. Participants One-hundred-ninety-two undergraduates at three universities participated in this online survey between November 2011 – April 2012. Methods Participants reported on their rape myth acceptance (RMA) and personal direct and indirect (i.e., disclosure receipt)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 33 publications
(63 reference statements)
1
51
0
1
Order By: Relevance
“…Within studies that did include males, this percentage ranged from 20·8% (Paul et al . )–51% (Garcia et al . ); the majority of studies were comprised of around 30–40% males.…”
Section: Resultsmentioning
confidence: 99%
“…Within studies that did include males, this percentage ranged from 20·8% (Paul et al . )–51% (Garcia et al . ); the majority of studies were comprised of around 30–40% males.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, people with rape experience were proven to be more empathetic towards a victim than those without personal victimization (Osman, 2011(Osman, , 2014Smith & Frieze, 2003). Women with victimization experience were shown to be more empathetic towards a female victim (Osman, 2011(Osman, , 2014Paul et al, 2014), but no gendered empathic differences were found for victimized men (Osman, 2011). Osman (2014 further reported that victimized women are more empathetic in acquaintance rape (but not in stranger rape).…”
Section: Rape Empathymentioning
confidence: 95%
“…Nonetheless, a large number of studies suggests that men are more likely to engage in victim blaming (e.g., Anderson & Lyons, 2005;Bendixen, Henriksen, & Nøstdahl, 2014;Black & Gold, 2008;Durán, Moya, Megías, & Viki, 2010;Ferrão, Gonçalves, Giger, & Parreira, in press;Gölge et al, 2003;Grubb & Harrower, 2009;Harrison, Howerton, Secarea, & Nguyen, 2008;Mitchell, Angelone, Kohlberger, & Hirschman, 2009;Paul, Kehn, Gray, & Salapska-Gelleri, 2014;Schneider, Mori, Lambert, & Wong, 2009;Strömwall, Landström, & Alfredsson, 2014;Yamawaki & Tschanz, 2005). …”
Section: An Overview Of Rape Victim Blaming Observer Gendermentioning
confidence: 99%
See 2 more Smart Citations